Solve the Following Equation: 6(6x - 5) - 5(7x - 8) = 12(4 - X) + 1 - Mathematics

Advertisement Remove all ads
Sum

Solve the following equation:

6(6x - 5) - 5(7x - 8) = 12(4 - x) + 1

Advertisement Remove all ads

Solution

6(6x - 5) - 5(7x - 8) = 12(4 - x) + 1

36x - 30 - 35x + 40 = 48 - 12x + 1

⇒ x + 12x = 49 - 10

⇒ 13x = 39 

⇒ x = `19/13`

⇒ x = 3

Concept: Simple Linear Equations in One Variable
  Is there an error in this question or solution?

APPEARS IN

Selina Concise Mathematics Class 8 ICSE
Chapter 14 Linear Equations in one Variable
Exercise 14 (A) | Q 16 | Page 165
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×